Assessing the Readiness of Student Learning Activity and Learning Outcome - Widodo Winarso (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
The research is proposed by the underestimate of the student activeness and the student's achievement. The purposes of the research were to evaluate the influence of the student readiness to the student activeness, the influence of the student readiness to the student achievement, and the influence of the student activeness to the student achievement in the first class of Junior High School 2 Cibingbin, Kuningan, West Java. Its influence uses the correlation descriptive method. The population is 127 students of the first class of Junior High School 2 Cibingbin, Kuningan, West Java and the sample is 96 students. The results of the study showed that the description of the student readiness learning was at high category 69.35%. The description of the student activeness was also at high category 85.47%. In addition, the description of the student achievement was categorized as high grade (84.35%). There was a positive influence of students readiness to the student's activeness and achievement, and there was the positive influence of the student's activeness to the student's achievement.